Preparation and characterization of molecularly imprinted solid amine adsorbent for CO2 adsorption. (21st May 2018) - Liu, Fenglei; Kuang, Yizhu; Wang, Shuoyu; Chen, Shuixia; Fu, Wenhao
Abstract : A molecularly imprinted solid amine adsorbent was successfully synthesized and exhibited excellent CO2 adsorption performance under simulated flue gas. Abstract : A molecularly imprinted solid amine adsorbent was successfully synthesized via a facile crosslinking reaction based on polyethyleneimine (PEI) as the skeleton, glycol diglycidyl ether (GDGE) as cross-linker and CO2 molecules as template. FT-IR, FT-Raman, 13 C NMR spectroscopy and TGA were employed to characterize the chemical structure and thermal stability of the solid amine adsorbent. The experimental results showed that the amine content of the molecularly imprinted polymer polyethyleneimine spheres (MIP-PEIs) could reach as high as 11.41 mmol g −1, and the material exhibited a lower CO2 diffusion resistance during CO2 adsorption. The CO2 adsorption capacity of MIP-PEIs (6.58 mmol g −1 ) was higher than that of non-imprinted NIP-PEIs (5.87 mmol g −1 ). The presence of water markedly increased the CO2 adsorption capacity by promoting the chemical adsorption of CO2 on the solid amine adsorbent. The pseudo-second order model could accurately describe the CO2 adsorption process on the MIP-PEIs from the beginning to the end. Moreover, this adsorbent also exhibited good regeneration performance, retaining almost the same adsorption amount of CO2 as the fresh material after ten adsorption–desorption cycles.